2000
DOI: 10.1038/sj.bmt.1702119
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and outcome of varicella-zoster virus infection in children after haematopoietic stem cell transplantation

Abstract: Summary:We report a retrospective analysis of VZV infection after haematopoietic stem cell transplantation (HSCT) in children. Thirty-three (30%) of the total 109 children who were transplanted during a 7 year period developed post-transplant VZV infection. Twenty-four of these 33 (73%) children had VZV infection within 1 year following HSCT. The cumulative incidences of post-transplant VZV infection at 1 and 5 years were 26% and 45%, respectively. The positive and negative predictive values of pretransplant V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 19 publications
6
73
3
Order By: Relevance
“…1 Infrequently, HZ infection is complicated by disseminated cutaneous involvement or visceral organ involvement with significantly increased morbidity and even mortality. 2,3 The incidence of HZ in children following HSCT has been reported in the range of 23-67%, [4][5][6][7][8][9] which is comparable to the incidence in adult HSCT recipients. Some studies have suggested that children develop post-HSCT HZ earlier than adults, 4,5,7 but other studies have demonstrated a later median time of onset.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…1 Infrequently, HZ infection is complicated by disseminated cutaneous involvement or visceral organ involvement with significantly increased morbidity and even mortality. 2,3 The incidence of HZ in children following HSCT has been reported in the range of 23-67%, [4][5][6][7][8][9] which is comparable to the incidence in adult HSCT recipients. Some studies have suggested that children develop post-HSCT HZ earlier than adults, 4,5,7 but other studies have demonstrated a later median time of onset.…”
Section: Introductionmentioning
confidence: 71%
“…The incidence of HZ in our cohort of pediatric HSCT patients is consistent with the incidence rates previously reported. [4][5][6][7][8][9] Additionally, our study demonstrates that although a substantial number of patients develop HZ in the early post-HSCT period, there is an increase in incidence over time and HZ can occur up to 5 years post-HSCT. This is particularly evident in the allogeneic cohort who, despite incidence rates of 34 and 50% at 12 months in all allogeneic patients and seropositive allogeneic patients, respectively, experiences a substantial increase over time such that 45 and 70% of these patients, respectively, have developed HZ by 60 months post-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations